The little mermaid greatest hits [compact disc] - Menken, Alan; Ashman, Howard; Slater, Glenn; Jepsen, Carly Rae, 1985- (Walt Disney Records, 2013)
Venture under the sea with Ariel and her friends with a collection featuring original music from the beloved Disney film as well as new songs inspired by the movie. Also included is a new version of Part of Your World sung by Carly Rae Jepsen.